ANALISIS MINAT BELAJAR SISWA KELAS V PADA PEMBELAJARAN MATEMATIKA MATERI PERSAMAAN GARIS LURUS - Mei Elisa Zahra Siregar; Atika Maulida; Aldi Aldi; M. Agus Syahputra; FadryanRaynal Zikri; Ilfan Syafawi; Dwi Novita Sari (LPSDI Bina Patria, 2023)
This study aims to determine the learning interest of fifth grade students in learning mathematics on straight line equations and to increase fifth grade students' interest in learning mathematics on straight line equations. This research is a descriptive research with a qualitative approach. This research was conducted in class V-B SD Ar-Rayhan School JL. Garu II NO-11A Medan Sandpaper. As for the participants in this study, namely class VB teachers and class VB students, totaling 25 people. Based on the results of the research, it can be concluded that students' learning interest in learning mathematics on the subject of straight line equations can be said to be low. Out of a total of 25 students in class V-B SD Ar-Rayhan School JL. Garu II NO-11A Medan Sandpaper, there were 15 students who did not have an interest in learning, especially in learning mathematics on straight line equations.